Δ(9)-Tetrahydrocannabinol concentrations in exhaled breath and physiological effects following cannabis intake - A pilot study using illicit cannabis - Coucke, Line; Massarini, Enrico; Ostijn, Zachery; Beck, Olof; Verstraete, Alain G (Clinical biochemistry, 2016)
Δ(9)-Tetrahydrocannabinol (THC) can be measured in exhaled breath by using an aerosol particle collection device. The sampling procedure is simple, non-invasive and takes only 2-3min. In the present study we measured the amount of THC in exhaled breath of cannabis users at specific time intervals up to 3h after smoking one cannabis cigarette. The breath concentration-effect relationship was studied by measuring the pulse rate and the pupil diameter to assess physiological changes. THC and the main metabolite 11-nor-9-carboxy-Δ(9)-tetrahydrocannabinol were analyzed in exhaled breath by a liquid chromatography-tandem mass spectrometry method. Thirteen subjects (9 males and 4 females, aged 23-24years) participated. Five of those were using cannabis more frequently than monthly. THC was detected in most subjects already at baseline, concentrations increased following smoking and remained detectable for over 3h (mean THC concentration in breath at 3h: 1479pg/sample). Pulse rate (p=0.015) and pupil diameter (p=0.044) were significantly altered up to 30min after smoking. The detection window of cannabis in breath after smoking one cannabis cigarette in occasional and chronic smokers was at least 3h. Only THC was detected, and not the metabolite. The THC concentration in exhaled breath was related to the physiological changes that occur over time. Exhaled breath can be used to detect recent cannabis exposure.